Evaluation of the effectiveness of the California mosquito-borne virus surveillance & response plan, 2009-2018. - Mary E Danforth; Robert E Snyder; Emma T N Lonstrup; Christopher M Barker; Vicki L Kramer (Public Library of Science (PLoS), 2022)
Local vector control and public health agencies in California use the California Mosquito-Borne Virus Surveillance and Response Plan to monitor and evaluate West Nile virus (WNV) activity and guide responses to reduce the burden of WNV disease. All available data from environmental surveillance, such as the abundance and WNV infection rates in Culex tarsalis and the Culex pipiens complex mosquitoes, the numbers of dead birds, seroconversions in sentinel chickens, and ambient air temperatures, are fed into a formula to estimate the risk level and associated risk of human infections. In many other areas of the US, the vector index, based only on vector mosquito abundance and infection rates, is used by vector control programs to estimate the risk of human WNV transmission. We built models to determine the association between risk level and the number of reported symptomatic human disease cases with onset in the following three weeks to identify the essential components of the risk level and to compare California's risk estimates to vector index. Risk level calculations based on Cx. tarsalis and Cx. pipiens complex levels were significantly associated with increased human risk, particularly when accounting for vector control area and population, and were better predictors than using vector index. Including all potential environmental components created an effective tool to estimate the risk of WNV transmission to humans in California.